DEVELOPING HALAL TOURISM BASED ON TRADITIONAL CULINARY HERITAGE: AN ISLAMIC LAW AND SWOT ANALYSIS OF CERTIFICATION COMPLIANCE IN TANGERANG, INDONESIA - Abdul Rachman; Muhammad Azizan Fitriana; Hidayat; Risyda Nurul Qolbi; Bilaly Sangare (al-Mawarid Jurnal Syariah dan Hukum (JSYH), 2026)
Purpose – This study aims to analyze the gap between the economic potential of traditional cuisine in the halal tourism ecosystem and the level of compliance of business actors with certification requirements, as stipulated in the Halal Product Guarantee Law. This study also examines the factors influencing the halal tourism ecosystem and halal guarantees among business actors in Laksa Tangerang. Methods – This study used a qualitative descriptive method with a normative juridical approach. The analysis was conducted by linking the culinary practices of Laksa Tangerang with SWOT analysis and halal product assurance regulations in Indonesia. Data were obtained through observations in the culinary tourism area in Laksa Tangerang, interviews with Laksa vendors, visitors, and the local community, and relevant literature. Findings – This study shows that the stagnation of halal culinary growth in Laksa Tangerang is caused by multidimensional structural constraints, including limited innovation, weak segmentation and promotion, and governance issues. The SWOT analysis identified several strategic strengths that position Laksa Tangerang as a potential hub for halal tourism development. From an Islamic law perspective, its integration into the halal tourism ecosystem requires formal halal certification as a Halal Product Guarantee, so that halal assurance is institutionalized in a credible manner. Therefore, strengthening halal literacy, expanding certification, and improving governance are prerequisites for transforming Laksa Tangerang into a competitive and sustainable halal culinary tourism destination. Research contribution/limitations – This study contributes to providing space for the actualization of sharia values in local economic practices and offers a contextual and applicable SWOT analysis framework. Originality/value – This research offers a new perspective on integrating traditional culinary heritage into the Islamic legal framework in a contextual manner, thereby offering a model for sustainable Halal tourism development.